Detection and quantification of probiotic strain Lactobacillus gasseri K7 in faecal samples by targeting bacteriocin genes - Treven, Primož; Turkova, Kristyna; Trmčić, Aljoša; Obermajer, Tanja; Rogelj, Irena; Matijašić, Bojana Bogovič (Folia microbiologica, 2013)
Lactobacillus gasseri K7 is a probiotic strain that produces bacteriocins gassericin K7 A and K7 B. In order to develop a real-time quantitative PCR assay for the detection of L. gasseri K7, 18 reference strains of the Lactobacillus acidophilus group and 45 faecal samples of adults who have never consumed strain K7 were tested with PCR using 14 pairs of primers specific for gassericin K7 A and K7 B gene determinants. Incomplete gassericin K7 A or K7 B gene clusters were found to be dispersed in different lactobacilli strains as well as in faecal microbiota. One pair of primers was found to be specific for the total gene cluster of gassericin K7A and one for gassericin K7B. The real-time PCR analysis of faecal samples spiked with K7 strain revealed that primers specific for the gene cluster of the gassericin K7 A were more suitable for quantitative determination than those for gassericin K7 B, due to the lower detection level. Targeting of the gassericin K7 A or K7 B gene cluster with specific primers could be used for detection and quantification of L. gasseri K7 in human faecal samples without prior cultivation. The results of this study also present new insights into the prevalence of bacteriocin-encoding genes in gastrointestinal tract.
Keywords: Feces; Real-Time Polymerase Chain Reaction; Healthy Volunteers; Sensitivity and Specificity; mužské pohlaví; DNA primery; Lactobacillus acidophilus; Bacteriological Techniques; bakteriociny; Adult; bakteriologické techniky; kvantitativní polymerázová řetězová reakce; Bacteriocins; ženské pohlaví; feces; Humans; senzitivita a specificita; dospělí; DNA Primers; Female; lidé; Male; zdraví dobrovolníci pro lékařské studie